2020
DOI: 10.1021/acs.langmuir.0c01707
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Kinetic Pathways to Agitated and Spontaneous Emulsification

Abstract: Emulsification of an oil (dodecane and diesel fuel) in salinized water was studied under turbulent and agitation-free conditions in the presence of a mixture of an ionic and a nonionic surfactant. The properties of the air−water and the oil−water interfaces were investigated using the methods of du-Nouy ring, drop resonance vibrometry, and Langmuir film balance that allowed pinpointing the relevance of certain interfacial properties in emulsification. Estimation of the droplet size and its distribution from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 107 publications
2
16
0
Order By: Relevance
“…The more plausible scenario is that the oil is injected into the aqueous phase as droplet via transient or persistent shake up events due to instabilities occurring at the interface. Such a picture was presented in our earlier publication 26 , where we conjectured that the inverted (water-in-oil) emulsions first fuse with the interfacial monolayer following which a curvature reversal (an instability) develops at the interface, thus triggering the phase inversion. Because of the difference of the interfacial tensions between the flat interface and the water-in-oil emulsion, we surmise that local heterogeneous Marangoni instability to play an important role in the explosive phase inversions as depicted in Figure 9 (A and B).…”
Section: Bathochromic and Hypsochromic Shifts: The Polybasic Characte...mentioning
confidence: 53%
See 3 more Smart Citations
“…The more plausible scenario is that the oil is injected into the aqueous phase as droplet via transient or persistent shake up events due to instabilities occurring at the interface. Such a picture was presented in our earlier publication 26 , where we conjectured that the inverted (water-in-oil) emulsions first fuse with the interfacial monolayer following which a curvature reversal (an instability) develops at the interface, thus triggering the phase inversion. Because of the difference of the interfacial tensions between the flat interface and the water-in-oil emulsion, we surmise that local heterogeneous Marangoni instability to play an important role in the explosive phase inversions as depicted in Figure 9 (A and B).…”
Section: Bathochromic and Hypsochromic Shifts: The Polybasic Characte...mentioning
confidence: 53%
“…While a tightly packed hydrocarbon chain occupies an area of about 0.2 𝑛𝑚 2 , one would expect that the average area per molecule in an emulsion or in a vesicle would be higher than this value as they would be more disordered. On the other hand, the average area occupied by the ethylene glycol group of the non-ionic surfactant should be greater than (0.6 𝑛𝑚 2 ), as obtained 26 from the surface pressure-area isotherm. The average area per molecule, as estimated on the basis of the number of hydrocarbon chains) range from 0.34 𝑛𝑚 2 𝑡𝑜 0.4 𝑛𝑚 2 for the emulsions and vesicles (Table 2 and S4).…”
Section: Bathochromic and Hypsochromic Shifts: The Polybasic Characte...mentioning
confidence: 90%
See 2 more Smart Citations
“…Hexadecane is soluble in TPM but insoluble in both water and methanol. 54 Therefore, hexadecane acted as a tracer molecule 55 dissolved in the TPM phase to identify droplet pinch-off from the interface. We found that mixtures of TPM and C16 emulsified spontaneously but that residual oil remained at the air−water interface (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%